The frequency of HLA alleles in a population of Inuit women of northern Quebec - Metcalfe, Stephanie (Co-Action Publishing, 2013)
BACKGROUND: Human leukocyte antigen (HLA) alleles code for proteins that are involved in the recognition of foreign antigens and activation of the immune system. The frequency of HLA alleles varies across different populations. OBJECTIVE: To describe the frequency of HLA alleles in a population of Inuit women of Nunavik, Quebec, Canada. DESIGN: A cohort of women was recruited from 4 different communities between January 2002 and December 2007. HLA-B*07, HLA-DQB1*03, DQB1*06:02, DRB1*13 and DRB1*15:01 alleles were typed by PCR sequence-specific primers (PCR-SSP) and HLA-E and G alleles were type by DNA-sequencing procedures. RESULTS: We obtained data on 524 participants. The most frequent HLA alleles in this population were HLA-E*01:03, HLA-G*01:04:01 and HLA-DQB1*03, and they were found in 89, 75 and 94% of the population, respectively. CONCLUSIONS: The distribution of HLA alleles in Nunavik, Quebec is unique when compared to other populations in Canada or around the world.